The comparison of maternal and neonatal outcomes between emergency and planned cesarean deliveries in women with placenta previa - Taşgöz, Fatma Nurgül; Yenigül, Nefise Nazlı; Kender Erturk, Nergis; Kırşan İleri, Emine and Yaşa, Fatma Nur (The European Research Journal, 2022)
Objectives: To compare maternal and neonatal outcomes concerning emergency or planned cesarean deliveries in pregnancies complicated by placenta previa (PP), and to evaluate factors related to blood transfusion requirement. Methods: Three hundred sixty-three women with PP with (n = 80) and without (n = 283) placenta accreta spectrum (PAS) who delivered between May 2016 and May 2021 were retrospectively reviewed. The patients were allocated to two main groups as PAS and non-PAS and into two subgroups as emergency cesarean delivery (ECD) and planned cesarean delivery (PCD). Results: One hundred twenty-eight deliveries were emergency and 155 were planned in non-PAS group. In PAS group 38 patients were delivered urgently and 42 were delivered as planned. General anesthesia was preferred more frequently in emergency cases. Gestational age, birth weight, and the 1st and 5th minute APGAR scores of the infants were significantly lower and neonatal intensive care unit (ICU) admission was significantly higher in the ECD cases (p < 0.001) in both PAS and non-PAS groups. The total amount of blood and blood product transfused (p = 0.005), length of hospital stay (p = 0.022) were higher in the ECD cases and adult ICU admission was significantly higher in the ECD cases in non-PAS group (p = 0.016). In multilinear regression analysis, the need for blood transfusion was found to increase with the number of previous cesarean sections, ECD, PP with PAS, general anesthesia, and uterine artery ligation. Conclusions: In placenta previa, which is an obstetric condition associated with serious maternal and neonatal morbidity and mortality, adverse maternal and neonatal outcomes increase in cases of emergency cesarean delivery.